British athletics muscle injury classification: a new grading system - Pollock, N.; James, S. L. J.; Lee, J. C.; Chakraverty, R. (British Journal of Sports Medicine, 2014)
The commonly used muscle injury grading systems based on three grades of injury, representing minor, moderate and complete injuries to the muscle, are lacking in diagnostic accuracy and provide limited prognostic information to the clinician. In recent years, there have been a number of proposals for alternative grading systems. While there is recent evidence regarding the prognostic features of muscle injuries, this evidence has not often been incorporated into the grading proposals. The British Athletics Muscle Injury Classification proposes a new system, based on the available evidence, which should provide a sound diagnostic base for therapeutic decision-making and prognostication. Injuries are graded 0-4 based on MRI features, with Grades 1-4 including an additional suffix `a`, `b` or `c` if the injury is `myofascial`, `musculo-tendinous` or `intratendinous`. Retrospective and prospective studies in elite track and field athletes are underway to validate the classification for use in hamstring muscle injury management. It is intended that this grading system can provide a suitable diagnostic framework for enhanced clinical decision-making in the management of muscle injuries and assist with future research to inform the development of improved prevention and management strategies.